Teachers’ Perceptions, Planning, and Implementation of Game-Based Learning in English Extracurricular Program (A Case Of Smp 40 Semarang) - Utami, Citra Putri; Anggani L. Bharati, Dwi (English Education Journal, 2020)
The present study was a case study which was aimed at investigating the teachers’ perceptions, planning, and implementation of Game-Based Learning (GBL) in the English extracurricular program in SMP 40 Semarang. The participants of this study were two teachers. The data were collected through questionnaire, interview, observations, and document analysis. The result showed that the two teachers mostly have the same perceptions of GBL with the experts and researchers. In the teaching planning, the teachers planned to give seven games in one semester program. The games were mostly in the form of cooperative and competitive games, and they were aimed improve speaking, listening, and writing skills. The lesson plans for each meeting included learning goal, time allotment, teaching materials, and classroom activities along with the scenario of teaching. In the real practices in the classroom, the teachers could successfully apply the games like in the planning. In evaluating the students, the teachers concerned on the students’ performances and product. Regarding the relation of the teachers’ perceptions, planning, and implementation, it was revealed that teachers’ perceptions influence the way the teachers implement GBL and teaching planning affects the successful GBL implementation. It is expected that further researchers may continue his study by involving more than one school with more subjects also.